A new technology for steel pipeline damage detecting without removing cladding. (15th July 2020) - Wang, Xinhua; Gu, Yaping; Chen, Yingchun; Ullah, Zia; Pan, Qingfeng; Zhao, Yizhen
Highlights: Harmonic signal generators is developed and harmonic magnetic field detection technology is proposed. Magnetic focusing array detection probe is designed. Inner and outer damage of in-service pipeline can be detected based on the proposed technology. Abstract: In this study, a harmonic magnetic field detection technology is proposed in order to detect the damage of an in-service coated steel pipeline. Based on the electromagnetic theory and magnetic field detection principle integrated with magnetic focusing technology, an array consisting of focusing detection probe and harmonic magnetic field detection system was designed. Numerical simulations for different coil structures was performed by finite element simulation technique to explore the focusing performance of designed coil structure. The feasibility of the detection probe and harmonic magnetic field detection technology was verified by experimental results and numerical simulations. The results of this study show that the proposed method can provide excellent information about the full wall thickness by penetrating the cladding over the surface of pipeline and effectively identify the outer wall defects and the inner wall corrosion.